Halal in Harmony: Indigenous Perspectives on Faith and Commerce in Zamboanga City - Eddie M. Ladja; Cherry Mae L. Ladja (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2024)
The global halal industry has become a key player in the Muslim economy, grounded in Islamic business ethics. Halal extends beyond dietary laws to include various products and services such as food, cosmetics, pharmaceuticals, and financial services. Consequently, halal-certified goods are increasingly popular among both Muslim and non-Muslim consumers, driven by a demand for ethical and high-quality products. This growth underscores the halal industry's potential to shape global consumer behaviors and ethical standards across multiple sectors. Despite this, some indigenous communities express skepticism regarding halal products. This skepticism is primarily rooted in concerns over halal goods produced by non-Muslim manufacturers and the lack of recognized halal certification labels. Such doubts can obstruct the acceptance and growth of halal products within these communities, highlighting the need for transparent certification processes and improved education about halal practices. To investigate these dynamics, this study employs a mixed-methods approach, incorporating both qualitative and quantitative research methods. In-depth interviews with 100 halal industry stakeholders across four Barangays of Dita, Calabasa, Muti, and Tictapul within the outskirt of Zamboanga City reveal diverse perspectives on halal practices, as well as associated challenges and opportunities. Additionally, focus group discussions involve participants from both Muslim and non-Muslim backgrounds to explore their attitudes towards halal products, purchasing motivations, and perceptions of quality and ethics. Surveys further gather data on consumer behavior and preferences regarding halal goods. Addressing transparency in halal certification, enhancing education on halal practices, and fostering cultural sensitivity among businesses are vital for building trust within skeptical communities. Collaborative partnerships among halal producers, indigenous communities, and market players can create shared knowledge and innovations, ultimately expanding the halal industry's reach and positively impacting the global economy.